PENGUKURAN KUALITAS PERANGKAT LUNAK APLIKASI SISFO_NILAI DI POLITEKNIK PIKSI GANESHA BERDASARKAN ISO 9126 - Lailela, Septi Noer; Kusumadiarti, Rini Suwartika (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2018)
The goal of this research is to measure quality of SISFO_Nilai software based on ISO 9126. Quality Measurement is based on 6 (six) characteristics: functionality, reliability, usability, efficiency, maintainability, and portability. Analytical method used in this research is descriptive statistics with quantitative approach. Data collection technique were carried out by distributing questionnaires to 119 respondents. Every indicator scored by respondents will be classified in five alternate responses by using Likert Scale, which eventually describe response rating. Validity test will be conducted using Pearson product-moment correlation statistic analysis. And reliability test will implement Cronbach Alpha statistic using SPSS software.The results of software quality measurements using the ISO 9126 standard, the actual percentage is an average of 69.97%, it can be concluded that SISFO_Nilai Software by ISO 9126 standards with an average criteria of "GOOD".The result of this research can be used by the institution as a reference in further development of SISFO_Nilai to achieve more optimum performance.